Research on Occupational Stress and Coping Skills Assessment of Industrial Workers in Selected Areas of Bhopal (M.P.) - Singh, Nama; Patel, Margi (Journal of Global Economy, Business and Finance, 2026)
The researcher felt a deep sense of satisfaction and fulfillment for having undertaken the study. The study provided the investigator with deeper insight about stress and coping skill among industrial worker. The direction from the guide, expert opinions and help from the staff of the college made the study interesting. This chapter deals with the major findings, discussion, conclusion, nursing implications, limitations, recommendations and summary drawn from the result of the study. The following chapter also deals with summary of the study. The present study attempts to find out the Occupational stress and coping skill by industrial workers. The sample consisted of total 60 industrial workers with stressful working condition. The tool used for assessing the stress was Perceived Stress Scale and Coping Scale. The majority of the industrial worker between two variables stress and coping skills. Stress mean is 22.216 and coping mean is 19.6 correlations (r) 0.667 positive correlations and table value is 0.250.